Role of the Educational Manager in High Schools in Cluj-Napoca as Centres of Excellence in the Local Community - Remus VĂIDĂHĂZAN; Iulia JULEAN; Velu-Sebastian BARTHA; Ancuța NUȚ (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae)
The Role of the Educational Manager in High Schools in Cluj-Napoca as Centers of Excellence in the Local Community. Educational management oversees the education system to ensure an effective learning environment by planning, organizing, coordinating, and controlling activities such as leading staff, managing resources, implementing policies, and engaging with the community. Educational leaders develop strategies to enhance programs and services, aiming to produce competent graduates ready for the workforce and significant societal roles, thereby improving the overall education system. Objective: This study explores high schools’ vision and mission, the educational manager’s role in shaping future competencies, and the strengths each institution promotes. It also examines the importance of parental involvement in education. The findings provide insights into strategic educational leadership and its impact on student development and institutional excellence. Materials and Methods: This study involved 10 directors (educational managers) selected from a total of 26 high schools in Cluj-Napoca. The data collection method chosen was structured interviews conducted based on a personal data processing agreement. The study was conducted from February to April 2023. Results: Highlighting the role of high schools as centers of excellence in the local community, this investigation can contribute to strengthening the connection between educational institutions and the surrounding community. It can promote collaboration, parental involvement, and community engagement in supporting and developing high schools. The results and conclusions of the investigation can provide valuable information for the development of educational policies at the local or regional level. They can serve as a foundation for the development of strategies and measures to support the development of high schools as centers of excellence and improve the quality of education. Conclusion: This investigation contributes to the field of education research by providing new knowledge and understanding of the role of the educational manager in high schools in Cluj-Napoca. It can inspire and stimulate further research and studies in the field of educational management and excellence in education.